Strategi Pengembangan Usaha Ayam Arab di Baranti, Sidenreng Rappang dengan Pendekatan Matriks I-E - Hajar; Nurhapsa; Mustafah, A. Erna Sri Wahyuningsih (Integrated and Sustainable Agriculture, 2024)
The main problems in developing the Arabian chicken farming business in the grower phase in Panreng Village are cultivation which still uses simple equipment, limited capital, risk of chicken death, and location close to residential areas. This research aims to formulate a business development strategy using SWOT analysis and the Internal-External (I-E) matrix. The methods include collecting primary and secondary data, analyzing internal and external factors, and formulating strategies based on IFAS and EFAS results. The IFAS analysis results show an average score of 2.79, with the main strengths being the ease of obtaining DOC raw materials and guaranteed harvest marketing. Meanwhile, the results of the EFAS analysis show an average score of 2.54, with the main opportunities being the high demand for Arabic chicken meat and increasing employment opportunities. Based on the I-E matrix and SWOT analysis, the business position is in quadrant I, indicating strong conditions and opportunities. Therefore, an aggressive strategy is recommended, including utilization of raw materials, increasing farmer motivation, and optimizing crop marketing. The implementation of this strategy is expected to increase the productivity and sustainability of the grower phase Arabian chicken farming business in Panreng Village.